2013
DOI: 10.1021/es304977m
|View full text |Cite
|
Sign up to set email alerts
|

Arsenic Methylation in Soils and Its Relationship with Microbial arsM Abundance and Diversity, and As Speciation in Rice

Abstract: Methylation of arsenic in soil influences its environmental behavior and accumulation by plants, but little is known about the factors affecting As methylation. As speciation was determined in the pore waters of six soils from diverse geographical locations over 54 days of incubation under flooded conditions. The concentration of methylated As (monomethylarsonic acid, MMA, and dimethylarsinic acid, DMA) varied from 0 to 85 μg L −1 (0 − 69% of the total As in pore water). Two Bangladeshi paddy soils contaminate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
128
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 187 publications
(135 citation statements)
references
References 56 publications
7
128
0
Order By: Relevance
“…It may therefore play an important role in the biogeochemistry of As cycling. arsM genes have been detected in soils using degenerate primers (29) or Geochip which contains probes for more than 60 arsM genes but not PaarsM (30). However, the degenerate primers used by Jia et al (29) could not amplify PaarsM from the genomic DNA of P. alcaligenes, likely due to the phylogenetic diversity and the limited As methylation sequences available.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It may therefore play an important role in the biogeochemistry of As cycling. arsM genes have been detected in soils using degenerate primers (29) or Geochip which contains probes for more than 60 arsM genes but not PaarsM (30). However, the degenerate primers used by Jia et al (29) could not amplify PaarsM from the genomic DNA of P. alcaligenes, likely due to the phylogenetic diversity and the limited As methylation sequences available.…”
Section: Discussionmentioning
confidence: 99%
“…More recently, degenerate primers based on the known diversity of arsM sequences from both prokaryotic and eukaryotic microbes have been designed for the purpose of identifying additional arsM genes (29). However, Pseudomonas arsM sequences were not included in the design of degenerate primers due to the lack of reference sequences from isolates in the genus (29,30).…”
mentioning
confidence: 99%
“…12 Distinct geographic patterns exist in methylated arsenic abundance in rice grains, with rice grown in the southcentral U.S. tending to have a large fraction of methylated arsenic, while Asian-grown rice accumulates primarily inorganic As (iAs). 2,8,13 The reasons for these patterns are unknown. Microbial arsenic methylation is catalyzed by arsenite Sadenosylmethionine methyltransferase (ArsM) enzymes 14 which mediate the sequential methylation of As(III) to mono-, di-, and trimethylated species.…”
Section: ■ Introductionmentioning
confidence: 99%
“…For example, environmental conditions influence the As methylation activity of microbes, while the abundance of As methylation microbes has little effect on As methylation. A previous study reported that the arsM gene copy number correlated positively with the soil pH [25]. Although there were more As methylated microbes in neutral alkaline soils, the activity of As methylation was higher in acidic soils.…”
Section: As Species Concentration Vs As Metabolism Gene Copy Numbersmentioning
confidence: 86%